2017
DOI: 10.1364/ao.56.007841
|View full text |Cite
|
Sign up to set email alerts
|

On-chip membrane-based GaInAs/InP waveguide-type p-i-n photodiode fabricated on silicon substrate

Abstract: Toward the realization of ultralow-power-consumption on-chip optical interconnection, two types of membrane-based GaInAs/InP p-i-n photodiodes were fabricated on Si host substrates by using benzocyclobutene bonding. A responsivity of 0.95 A/W was estimated with a conventional waveguide-type photodiode with an ∼30-μm-long absorption region. The fitting curves based on the experimental data indicated that an absorption efficiency above 90% could be achieved with a length of 10 μm. In addition, increased absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…DWB of III-Vs on Si offers a Si-CMOS-compatible solution for integrated optics with potential for low-cost-high-scalability fabrication. Several optoelectronic devices using wafer bonding have been proposed and demonstrated, from electrically pumped lasers [11], [12], [14], [64]- [70], to modulators [71], [72], amplifiers [73], [74], and PDs with high responsivity or bandwidth [75], [76].…”
Section: Integrated Iii-v Optoelectronicsmentioning
confidence: 99%
“…DWB of III-Vs on Si offers a Si-CMOS-compatible solution for integrated optics with potential for low-cost-high-scalability fabrication. Several optoelectronic devices using wafer bonding have been proposed and demonstrated, from electrically pumped lasers [11], [12], [14], [64]- [70], to modulators [71], [72], amplifiers [73], [74], and PDs with high responsivity or bandwidth [75], [76].…”
Section: Integrated Iii-v Optoelectronicsmentioning
confidence: 99%
“…Structures similar to the membrane laser can be used. Figure 18(a) shows a microscope image of a fabricated membrane photodiode with a lateral diode scheme [99,100]. The structure is basically as same as that of the DR membrane lasers, except for the introduction of a GaInAs bulk absorber instead of the QWs.…”
Section: Photodiodes Based On Membrane Laser Stacksmentioning
confidence: 99%
“…However, a shorter length gives a lower responsivity. To maintain enough responsivity, even with short device length, introductions of DBR and PhC structures were proposed and demonstrated [100,101]. With these structure, fF-level capacitance can be realized.…”
Section: Photodiodes Based On Membrane Laser Stacksmentioning
confidence: 99%
“…Recently, we reported that the introduction of a photonic crystal structure into the in-plane p-i-n PD would provide strongly enhanced lateral optical confinement or the slow-light effect of the GaInAs absorber, resulting in a narrower stripe width for achieving sufficient absorption efficiency. 16,17) A t r limitation of 70 GHz is calculated by assuming a fully depleted absorption region with a stripe width of 0.3 µm, in which a saturation hole drift velocity of 4.8 × 10 6 cm=s is assumed to be obtained in the presence of a sufficient electric field. 18) Figure 6(b) shows another estimation of the 3 dB bandwidth of the receiverless PD, which is expected to be introduced in future on-chip optical interconnections.…”
mentioning
confidence: 99%